2013
DOI: 10.1016/j.jpeds.2013.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Haemophilus influenzae Type b Conjugate Vaccine in Low- and Middle-Income Countries: Regional Analysis and Assessment of Major Determinants

Abstract: Objectives To estimate the cost-effectiveness of Haemophilus influenzae type b (Hib) conjugate vaccine in low-and middle-income countries and identify the model variables, which are most important for the result. Study design A static decision tree model was developed to predict incremental costs and health impacts. Estimates were generated for 4 country groups: countries eligible for funding by the GAVI Alliance in Africa and Asia, lower middle-income countries, and upper middle-income countries. Values, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…This analysis revealed that the cost-effective vaccine price for an infant-targeted vaccine would be in a similar range to those prices charged for other vaccines (<$10) (28,29). Adolescent/adult-targeted vaccine could be priced at a higher level, but still less than the price of human papillomavirus vaccines (<$50) (30).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This analysis revealed that the cost-effective vaccine price for an infant-targeted vaccine would be in a similar range to those prices charged for other vaccines (<$10) (28,29). Adolescent/adult-targeted vaccine could be priced at a higher level, but still less than the price of human papillomavirus vaccines (<$50) (30).…”
Section: Discussionmentioning
confidence: 82%
“…Our regression analysis method for approximating treatment and productivity costs in all study countries has been used in previous studies (27,28), and we consider these results to be relatively robust estimates despite heterogeneity between studies. Less evidence is available about vaccine delivery costs, particularly for mass campaigns, and we had to make relatively crude assumptions about this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important clinical manifestations of Hib are meningitis, pneumonia, and other non-meningitis-non-pneumonia (NMNP) diseases like septicemia, orbital cellulitis, septic arthritis, osteomyelitis, and sinusitis [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Griffiths et al identified key determinants that drive cost-effectiveness analysis for Hib vaccine, based on a user friendly model that makes it easier for countries to conduct such analysis. 13 The analysis from India 14 reveals the high cost-effectiveness of the vaccine, using various scenarios. Fortunately, and after a long delay, India has introduced Hib vaccine in late 2011 in 2 states and 6 additional states are planning to introduce the vaccine by the end of 2012.…”
mentioning
confidence: 99%